WELCOME: improving WEight controL and CO-Morbidities in children with obesity via Executive function training: study protocol for a randomized controlled trial - Tiffany Naets; Leentje Vervoort; Marijke Ysebaert; Annelies Van Eyck; Stijn Verhulst; Luc Bruyndonckx; Benedicte De Winter; Kim Van Hoorenbeeck; Ann Tanghe; Caroline Braet (BMC, 2018)
Abstract Background Obesity is a widespread problem that not only leads to medical and psychological diseases in adults, but also in children and adolescents at an early stage in life. Because of its global burden on both the individual and society, it is necessary to develop effective evidence-based treatments. Current "Multidisciplinary Obesity Treatments" (MOT) already provide significant weight loss, but still leave room for more long-lasting improvements. In this protocol paper, we outline the research goals of the WELCOME trial, based on a substantial proof of concept. Methods In this Randomized Controlled Trial (RCT) - conducted in both an inpatient and two outpatient treatment settings - existing MOT will be supplemented with an Executive Function (EF) training and compare effects on various parameters in an experimental versus an active control group of obese youngsters (8-18 years old). WELCOME aims to (a) train youngsters' executive functions to facilitate effects on weight loss, psychological and medical comorbidities, (b) to enhance the long-term effects by continuing the training in the daily home context with booster sessions, and (c) to investigate its effects until a 6-month follow-up. In comparison to the active control group, better progress is expected in the experimental group on following variables: weight, psychological comorbidities (unhealthy eating behavior, internalizing symptoms, impaired self-esteem) and medical comorbidities (metabolic syndromes, endothelia dysfunction, tonsillar hypertrophy and sleep obstruction). Discussion It is stated that this EF-training for enhancing self-control abilities is necessary for a long-lasting effect of childhood obesity treatment interventions. Trial registration The Study Procotol was registered on 10/05/2017 (n° ISRCTN14722584).